2020
DOI: 10.1101/2020.05.27.119990
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Novel antioxidant therapy with the immediate precursor to glutathione, γ-glutamylcysteine (GGC), ameliorates LPS-induced cellular stress in anin vitrocystic fibrosis model

Abstract: IntroductionGlutathione deficiency and chronic bacterial inflammation exacerbates the oxidative stress damage to airways in cystic fibrosis. Improvements to current antioxidant therapeutic strategies are needed. Dietary supplement, γ-glutamylcysteine (GGC), the immediate precursor to glutathione, rapidly boosts cellular glutathione levels following a single dose in healthy individuals. Efficacy of GGC against Pseudomonas aeruginosa derived lipopolysaccharide (LPS), a prominent factor in mediating both bacteria… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…The presence of oxidative stress in the lung in CF is very well described and plays a pivotal role in the pathogenesis of disease, and there are emerging data that demonstrate cellular lipid metabolism is also disrupted in CF [ 5 , 45 ]. The propensity for ferroptosis in CF is probably directly linked to CFTR dysfunction, which is associated with reduced activity of γ-glutamylcysteine synthetase (GCS) and decreased ability to import cysteine into the cell, which are both required for GSH biosynthesis [ 11 , 46 , 47 ]. Consistent with this, we found that IB3-1 cells had lower intracellular levels of GSH than their cognate C38 cells at baseline and GSH levels were further reduced by FAC and erastin treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of oxidative stress in the lung in CF is very well described and plays a pivotal role in the pathogenesis of disease, and there are emerging data that demonstrate cellular lipid metabolism is also disrupted in CF [ 5 , 45 ]. The propensity for ferroptosis in CF is probably directly linked to CFTR dysfunction, which is associated with reduced activity of γ-glutamylcysteine synthetase (GCS) and decreased ability to import cysteine into the cell, which are both required for GSH biosynthesis [ 11 , 46 , 47 ]. Consistent with this, we found that IB3-1 cells had lower intracellular levels of GSH than their cognate C38 cells at baseline and GSH levels were further reduced by FAC and erastin treatment.…”
Section: Discussionmentioning
confidence: 99%